Kajian jaringan kawalan pugak bagi negeri Sarawak - Mustafar, Mohamad Asrul (2005)
The need for a proper levelling network has been the key requirement for modernizing the levelling infrastructure in the state of Sarawak. This thesis is aimed, firstly, to investigate and analyse the status of levelling data in Sarawak and to create a proper documentation of it. Secondly, the aim of the thesis is to study the potential use of GPS, combined with the newly establish precise geoid and the existing levelling network in Sarawak. Up to September 2002, DSMM Sarawak has already completed 19 lines of precise levelling and 55 lines of second-class levelling. Statistical test and pre-adjustment of the network are performed to analyse quality of the levelling data. The poor levelling network have caused difficulty in errors detection of levelling data. There are nine height differences in precise levelling data that still consist gross errors. GPS height transfer technique for 0.5-1.5 km baselines length were carried out for solving the problems of height transfer for river crossing. GPS measurements are performed for one and two hours using EGM96 and precise geoid model, WMG03A. Two hours observation using precise geoid gave consistent results and giving RMS differences of about ±1.4mm. Vertical datum biases are computed using GPS data on the second class benchmarks. Relative vertical datum biases are inconsistent for distances less than 10km. Bias that less than 15ppm is showed for distances 10 – 55km with geoid height differences 0.2 – 1.3m. The geoid height differences less than 0.2m represents bias below than 2ppm. This finding become as a guide for designing a network combine conventional and GPS levelling.